Poverty Reduction Through Self Employment of Women : A Study on Thengamara Mohila Sabuj Sangha (TMSS) - Siddique, MAJ; Salehin, MM; Ahmed, JU; Islam, AHMS (Progressive Agriculture, 2013)
The study was designed to present the issues of self-employed women of Thengamara Mohila Sabuj Sangha (TMSS) in Shajahanpur Upazila of Bogra district considering their participation in different programmes of TMSS for poverty alleviation. The impact of the study was assessed in terms of economic and social gains accrued by the womens and their family activities. Data were collected randomly from four villages under Shajahanpur Upazila of Bogra district. Sixty members from ten societies consisted of 292 members were selected randomly. The test of mean difference, head count ratio, poverty gap were used towards poverty alleviation. The study revealed that per household annual average income was positively changed. The expenditure and saving pattern indicated a shift of positive attitude towards life and improvement in the standard of living due to womens contribution. The poverty situations also improved as compared with that of the national level. This small effort is an addition to the knowledge about the essential contribution of the self employed women in different programmes to their role and status in the society which helps to reduce poverty. Finally, some recommendations were also made by the study. DOI: http://dx.doi.org/10.3329/pa.v19i1.17366 Progress. Agric. 19(1): 155 - 168, 2008